Provision of Anti-Tuberculosis Treatment on Nutritional Status in Children with Pulmonary Tuberculosis at Dr. Moewardi Hospital, Surakarta, Central Java - Ni Nyoman Ratna Sri Dewi; Pitra Sekarhandini; Aisya Fikritama Aditya (Journal of Maternal and Child Health, 2025)
Background: Tuberculosis caused by Mycobacterium tuberculosis, remains a significant global health issue. In Indonesia, the number of childhood TB cases has risen substantially from 33,366 in 2020 to 56,622 in 2022. TB can contribute to nutritional disorders, while treatment with anti-tuberculosis drugs (OAT) may help improve nutritional status. This study aims to evaluate the differences in nutritional status among toddlers with pulmonary TB before and after receiving OAT treatment at Dr. Moewardi Regional General Hospital, Indonesia.        Subjects and Method: This study utilized a comparative analytical design with a cross-sectional approach and employed a retrospective purposive sampling technique. It was conducted at Dr. Moewardi Regional General Hospital from 2017 to 2024 using a total sampling method, identifying the nutritional status of toddlers before and after OAT administration. The dependent variable was anti-tuberculosis drugs (OAT) treatment The independent variables was nutritional status Resulting in 42 samples that met the inclusion and exclusion criteria for toddlers aged 1–5 years. Data were processed using SPSS and analyzed with the Wilcoxon signed-rank test. Results: The male gender was higher by 25 people (59.52%) and female by 17 people (40.47%). The highest age sample of toddlers before treatment was 2 years (33.33%) and after treatment 3 years (33.33%). The highest nutritional status before OAT treatment was malnutrition (59.52%) while after treatment it was good nutrition (66.66%). The nutritional status of toddlers was higher (Mean = 2.90; SD = 0.57) than before (Mean = 2.12; SD = 0.63), and this result was statistically significant (p<0.001). Conclusion: There is a significant differences between the nutritional status of toddlers suffering from pulmonary tuberculosis before and after OAT treatment at Dr. Moewardi Regional General Hospital.